The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1073/pnas.1519246113
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl esters stabilize human CD1c conformations for recognition by self-reactive T cells

Abstract: Cluster of differentiation 1c (CD1c)-dependent self-reactive T cells are abundant in human blood, but self-antigens presented by CD1c to the T-cell receptors of these cells are poorly understood. Here we present a crystal structure of CD1c determined at 2.4 Å revealing an extended ligand binding potential of the antigen groove and a substantially different conformation compared with known CD1c structures. Computational simulations exploring different occupancy states of the groove reenacted these different CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 55 publications
3
67
0
Order By: Relevance
“…Site-directed mutagenesis was subsequently performed on the TCRα-chain to yield a complete GEM1 TCRα sequence (TRAV1-2, accession JQ778263.1), using the following primers: forward 5'-GCCGTGC-GGGTCACCGGCGGCT-3', reverse 5'-AGCCGCCGGTGACCCGCACGGC-3'. LDN5-TCRα and TCRβ (TRAV17/TRBV4-1) was cloned as previously described (47).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Site-directed mutagenesis was subsequently performed on the TCRα-chain to yield a complete GEM1 TCRα sequence (TRAV1-2, accession JQ778263.1), using the following primers: forward 5'-GCCGTGC-GGGTCACCGGCGGCT-3', reverse 5'-AGCCGCCGGTGACCCGCACGGC-3'. LDN5-TCRα and TCRβ (TRAV17/TRBV4-1) was cloned as previously described (47).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Soluble TCR and TCR dextramers: Generation of TCR heterodimers were performed as previously described (47). Briefly, the extracellular domains of TCRα and TCRβ chains were produced in E.coli Rosetta as inclusion bodies after cloning into the bacterial expression vector pGMT7.…”
Section: Submission Pdfmentioning
confidence: 99%
See 1 more Smart Citation
“…CD1b-autoreactive T cells can recognize phospholipids (17,19), and a higher frequency of sulfatide and monosialotetrahexosylganglioside-specific (GM1-specific) T cells was detected in multiple sclerosis patients compared with normal controls (26). Moreover, CD1c-restricted T cells specific for cholesteryl esters have recently been identified (31). Finally, most CD1d-restricted NKT cells also exhibit autoreactivity and A large proportion of human T cells are autoreactive to group 1 CD1 proteins, which include CD1a, CD1b, and CD1c.…”
Section: Introductionmentioning
confidence: 99%
“…29 In addition, recent studies have shown that CD1a-restricted human T cell clones recognize skin-derived apolar oils and phospholipids; autoreactive CD1b-restricted human T cell clones recognize a range of phospholipids, whereas CD1c-reactive clones can bind cholesterol and its esters. [31][32][33] Considering that these lipids accumulate in most tumors, it is imperative to explore the role of autoreactive group 1 CD1-restricted T cells in tumor immunity. This would shed light on the potential use of these T cells in cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%